2017
DOI: 10.1007/s11695-017-2660-3
|View full text |Cite
|
Sign up to set email alerts
|

RYGB Produces more Sustained Body Weight Loss and Improvement of Glycemic Control Compared with VSG in the Diet-Induced Obese Mouse Model

Abstract: Objective To compare the effects of murine models of vertical sleeve gastrectomy (VSG) and Roux-en-Y gastric bypass (RYGB) surgery on body weight, body composition, food intake, energy expenditure, and glycemic control. Background Weight regain and type-2 diabetes relapse has been reported in a significant proportion of VSG patients in some studies, but definitive conclusions regarding the long-term comparative effectiveness of VSG and RYGB are lacking both in humans and rodent models. Methods VSG, RYGB, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 41 publications
10
31
0
Order By: Relevance
“…Similar to other reports [12,19,20], body weight and food intake were both declined within first 2 weeks in Sham group, then turned to increasing thereafter, indicating the impact of surgical stress lasted for 2 weeks in this study. Mice in RYGB group, however, continue to loss weight until 5 weeks after surgery.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar to other reports [12,19,20], body weight and food intake were both declined within first 2 weeks in Sham group, then turned to increasing thereafter, indicating the impact of surgical stress lasted for 2 weeks in this study. Mice in RYGB group, however, continue to loss weight until 5 weeks after surgery.…”
Section: Discussionsupporting
confidence: 91%
“…Unlike the mice in Sham group regained all the lost weight and became 16±2% heavier at 12 weeks after surgery, body weight of the mice in RYGB group were kept at its lowest level in the whole postoperative period despite the food intake increased to be the same as Sham group. These findings demonstrated that RYGB is effective on long-term body weight loss which is consistent with clinical studies [12,19,20].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Weight regain and type-2 diabetes relapse has been reported in a significant proportion of VSG both in patients and in mice ( Felsenreich et al, 2016 ). Further, VSG is less effective to lastingly suppress body weight and improve glycemic control compared with RYGB in mice ( Hao et al, 2017 ). Together with our observation that EDGB provides a metabolic benefit identical to RYGB, these findings suggest that EDGB may be a better approach for weight reduction and glycemic control relative to VSG, although the long-term effects remain to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…VSG is rapidly gaining popularity with a trend to replace RYGB surgery because of its less damage and fewer complications. However, studies in mice have found that VSG is less effective for lasting reduction in body weight and improvement on glycemic control relative to RYGB, the gold standard surgery, in mice ( Hao et al, 2017 ). Further, removal of majority of the stomach renders it impossible to reverse the procedure in case complications such as anemia and severe bone loss occur ( Angrisani et al, 2015 , Buchwald et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%